The impact of customer capital on company's market value: An empirical study from 100 U.S. stock market leaders - Serhii Lehenchuk; Tetiana Zavalii (International Journal of Management and Economics, 2021)
The aim of the paper is to establish the relationship between the customer capital and the company's market value (MV). Examining this impact seems justified as the topic has been rarely investigated till now. The regression analysis was used to achieve the research objective. We analyzed reports of 100 U.S. stock market leaders for 2018, which were prepared in accordance with the requirements of International Financial Reporting Standard 3 "Business Combinations" and included information about customer capital. The hypothesis that the customer capital has a direct impact on the company's MV is confirmed by the results of this study. The proposed regression model (Model 3) can be used for needs of value-based management. Customer capital as a tool of value-based management is a poorly studied topic in the context of understanding the importance of the role of intangibles in creating value for company.
Keywords: D24; E22; G32; L14; 650; customer capital; goodwill; intangible assets; market value; research and development costs